Levinus Clarkson papers - Clarkson, Levinus
Chiefly business correspondence (1772 October 19-1793 January 3) of Clarkson with William Neate, merchant of London, England, and his father-in-law, David Van Horne, merchant, of New York, N.Y., relating to economic conditions and the slave trade. Includes letters (1784-1790) of Jacob Reade to his sister, Ann Van Horne, and various financial records.
Merchant and slave trader of Charleston, S.C.
Collection material in English.
Keywords: Neate, William -- Correspondence; Reade, Jacob -- Correspondence; Van Horne, Ann -- Correspondence; Van Horne, David -- Correspondence; Merchants -- Great Britain; Merchants -- New York (State) -- New York; Merchants -- South Carolina; Slave-trade -- South Carolina -- Charleston; Charleston (S.C.) -- Commerce; Great Britain -- Commerce; Great Britain -- Economic conditions -- 18th century; London (England) -- Commerce; New York (N.Y.) -- Commerce; New York (N.Y.) -- Economic conditions -- 18th century; South Carolina -- Economic conditions -- 18th century; Merchants; Slave traders